Amphibians from a tropical dry forest: Arenillas Ecological Reserve, Ecuador [Anfibios de un bosque seco tropical: Reserva Ecológica Arenillas, Ecuador] - Jara Guerrero, A. (2016)
Arenillas Ecological Reserve (Reserva Ecológica Arenillas - REA) is located in southwestern Ecuador, close to the Peruvian border, and belongs to the Tumbesian Endemism Region and is one of the last remnants of tropical dry forests at altitudes below 100 m a.s.l. Climate is characterized by a rainy season extending from January to May and a dry season extending from June to December. Few studies on the amphibians from the reserve have been made so far. Over a period of twelve months, from 2014 to 2016, we investigated the distribution of amphibians in the REA using regular visual and acoustic survey techniques as well as pitfall traps. Nine species belonging to five families were inventoried, most of them active only during the rainy season. At odds with the usual tropical amphibian communities structure with high species richness but low number of individuals, REA is characterized by a low number of species with a very high number of individuals. Along with species typical for the Tumbesian region, i.e. species specially adapted to dry environments, in the reserve occur also widespread species which are encountered usually in rain forests. © 2016 Los Autores.